2011
DOI: 10.5155/eurjchem.2.1.109-112.147
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and viscometric studies of flavonoids interactions with DNA at physiological conditions

Abstract: KEYWORDSCyclic voltammetric behaviour of three flavonoids: quercetin, morin and rutin was investigated for their interaction with DNA at pH = 4.7 and pH = 7.4 at body temperature (310 K), using glassy carbon electrode. The diffusion coefficients of the free and DNA bound forms of the flavonoids were evaluated using Randles-Sevcik equation. The binding parameters like binding constant, binding site size and binding free energy were also determined from voltammetric data. Moreover, the binding modes of flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, the possibility that an optimal FLP-DNA binding mode requires more specific sequences of three or more nucleotides, a structural signature that is more typical for groove binders than intercalating agents, was not ruled out . In the case of QUE interacting with monomeric and dimeric G-quadruplexes (G4-DNAs), absorption, fluorescence, circular dichroism (CD), and 1 H NMR spectroscopies revealed that QUE is stacked with the terminal tetrads of monomeric G4-DNAs due to intercalation and is bound to dimeric G4-DNAs due to groove binding . These experimental observations raise the following issue: Does the optimal binding of flavonoids to DNA involve the elements of both intercalation and groove binding?…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility that an optimal FLP-DNA binding mode requires more specific sequences of three or more nucleotides, a structural signature that is more typical for groove binders than intercalating agents, was not ruled out . In the case of QUE interacting with monomeric and dimeric G-quadruplexes (G4-DNAs), absorption, fluorescence, circular dichroism (CD), and 1 H NMR spectroscopies revealed that QUE is stacked with the terminal tetrads of monomeric G4-DNAs due to intercalation and is bound to dimeric G4-DNAs due to groove binding . These experimental observations raise the following issue: Does the optimal binding of flavonoids to DNA involve the elements of both intercalation and groove binding?…”
Section: Introductionmentioning
confidence: 99%